A DC/DC buck-boost converter-inverter-dc motor control based on model-free PID controller tuning by adaptive safe experimentation dynamics algorithm - Mohd Riduwan, Ghazali; Mohd Ashraf, Ahmad; Mohd Helmi, Suid; Mohd Zaidi, Mohd Tumari (Institute of Electrical and Electronics Engineers Inc., 2022)
Model-free PID control is currently utilized for the examination of a DC/DC Buck-Boost Converter-Inverter-DC motor structure in this study through optimization of the adaptive safe experimentation dynamics (ASED) method. PID controller has been popularized on its uncomplicated construct, convenient employment with limited tuneable parameters, and broad applicability to diverse mechanistic circumstances. Demonstrated nonlinearity, complexity, and high dimensional parameters within MIMO structure of the DC/DC Buck-Boost Converter-Inverter-DC motor then demand controller with immense precision. The ASED method is hereby adopted as the optimization approach with considerable precision as needed towards fine-tuning the PID controller for its ability to minimize both output of control tracking and energy consumption at reduced processing interval by the exclusion of mathematical modeling in assessing input and output of the system. Traced outcomes regarding voltage of the converter and bidirectional angular velocity are further accounted for performance appraisal of the recommended motor system equipping model-free PID controller following optimization of the ASED approach. A comparison was further operationalized between the proposed ASED approach and its conventional SED-based counterpart. Convergence stability was successively reached by the proposed approach via undertaken simulation with minimization of the specified objective function. Acquired results hereby confirmed smaller values of the objective function and total norm error by the ASED approach towards the precision of operation tracing against the performance of its conventional counterpart.